2015
DOI: 10.1039/c5cc05436b
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-catalyzed nucleophilic fluorination of halobenzenes

Abstract: The first π-coordination-catalyzed nucleophilic fluorination of unactivated aryl halides has been demonstrated. Chlorobenzene reacts with alkali metal fluorides (CsF, KF) in the presence of a Cp*Ru catalyst at 120-180 °C to give fluorobenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 39 publications
(22 reference statements)
0
19
0
1
Order By: Relevance
“…This effect is due to the electronwithdrawing nature of the [(h 5 -Cp*)Ru] þ fragment. In this way the [(h 5 -Cp*)Ru] þ group has been shown previously to catalyze the conversion of aromatic carboxylic acids in ethanol to ethyl esters [8,32], benzaldehydes in methanol to benzaldehyde dimethyl acetals [27], aromatic isocyanates to carbamates [20], and aromatic chlorides to fluorides [33]. During the present study the carbonyl carbon electrophile of complex (1) was found to be a versatile starting material for a range of nucleophilic substitution reactions involving nucleophiles such as alcohols, primary and secondary amines and aromatic sulfonamides.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…This effect is due to the electronwithdrawing nature of the [(h 5 -Cp*)Ru] þ fragment. In this way the [(h 5 -Cp*)Ru] þ group has been shown previously to catalyze the conversion of aromatic carboxylic acids in ethanol to ethyl esters [8,32], benzaldehydes in methanol to benzaldehyde dimethyl acetals [27], aromatic isocyanates to carbamates [20], and aromatic chlorides to fluorides [33]. During the present study the carbonyl carbon electrophile of complex (1) was found to be a versatile starting material for a range of nucleophilic substitution reactions involving nucleophiles such as alcohols, primary and secondary amines and aromatic sulfonamides.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…Die Balz-Schiemann-Reaktion, [14] bei der Aryldiazoniumsalze als Substrate ein Sicherheitsrisiko darstellen, wird immer noch häufig fürd ie Synthese von Arylfluoriden eingesetzt. Fortschritte bei der nukleophilen aromatischen Substitution ermçglichten kürzlich die Verwendung von Arylhalogeniden [15] und Phenolen [16] als geeignete Vorläufer fürArylfluoride.Die Fluorierung von Arylboronsäuren erfordert bisher eine stçchiometrische Tr ansmetallierung zu Cu I ,C u II ,P d II oder Ag I ,g efolgt von einer elektrophilen Fluorierung. [17] Ein katalytisches Beispiel mit mit Pd II ist eine Ausnahme;dieses beruht auf einem SETouter-sphere-Mechanismus und entspricht nicht dem in Schema 3g ezeigten Katalysezyklus.…”
Section: Methodsunclassified
“…From spectroscopic data, we inferred complex 53 a as the active intermediate. In a related study, Grushin achieved a catalytic fluorination of aryl chlorides via S N Ar (Table 1, Entry 6) [56] . Using the pre‐catalyst [Cp*Ru(η 6 ‐naphthalene)][BF 4 ] and CsF as the nucleophilic fluoride source, the reaction proceeded at 140 °C in dry DMF, via intermediates 54 a and 54 b , with a catalytic turnover number (TON) of 4.3 after 24 hours.…”
Section: Catalytic Transformations Via Transient η6‐coordinationmentioning
confidence: 99%